The Level Of Physical Fitness Of UPMI Medan PJKR Students After The Covid-19 Pandemic - Priono, Joko; Siregar, Imanuddin; Daulay, Dicky Edwad; Siregar, Epi Supriyani; Aliriad, Hilmy (Universitas Trunojoyo Madura, 2023)
This research is a descriptive research type with a research objective to determine the level of physical fitness of PJKR UPMI Medan students for the 2021/2022 Academic Year. This research is qualitative research using test observation sheets and measurements in collecting data and using 25 PJKR UPMI Medan students. This study obtained the results of the physical fitness level test for PJKR UPMI Medan semester one students. The scores had a good score category with 14 students (56%) of the total 25 respondents. Thus, the results of the physical fitness level test for PJKR UPMI Medan Semester 1 student after the Covid-19 Pandemic can be categorized as Good